Monosodium glutamate depresses the function of female reproductive system in rat by promoting oxidative stress induced changes in the structure of uterus - MUKTI MONDAL,; KAUSHIK SARKAR,; PARTHA PRATIM NATH,; GOUTAM PAUL, (International Journal of Pharma and Bio Sciences, 2016)
The aim of the present study was to examine the effects of MSG on the function of the uterus. We have observed significant degenerative changes in the endometrial and myometrial layers of the uterus in MSG exposed rats in a dose dependent manner compared to wall structure of the uterus of control rats. To elucidate the causes of MSG induced necrosis of the uterine wall structure, the activities of the cellular oxidative stress indices in MSG exposed uterus have been studied. We have found significant decrease in the activities of SOD, CAT, GR and GPx, and significant increase in the activity of GST in MSG exposed uterine tissue homogenate. Besides, the level of MDA in MSG exposed uterine tissue homogenate has been increased significantly. The results suggest that the degeneration of MSG induced uterine tissue might be due to enhanced oxidative stress and increased lipid peroxidation in uterine tissue cells. In conclusion, MSG depresses the function of female reproductive system in rats probably by promoting oxidative stress induced changes in the wall structure of uterus.